Reverse Left Ventricular Remodeling after Aortic Valve Replacement for Aortic Disease: TAVR and Minimally Invasive Cardiac Surgery - Oleksandra V. Telehuzova; Oleksandr S. Stychynskyi (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To examine the difference in left ventricular (LV) reverse remodeling parameters in elderly patients (65 years and more) who underwent transcatheter aortic valve replacement (TAVR) and minimally invasive cardiac surgery aortic valve replacement (MICS-AVR).Materials and methods. This study analyzed data from a consecutive series of 159 patients who underwent TAVR (n = 109) and MICS-AVR (n = 50) due to severe or critical aortic stenosis between January 2018 and August 2023. We also included the data from follow-ups: 30 days, 60 days and 1 year after replacement.Results. Five deaths (4.0%) occurred during the follow-up period of 3.1 ± 2.0  years. The causes of late death were stroke (n = 2), sepsis, interstitial pneumonia, and cancer. The 6-year survival rate was 86.0% and the 6-year freedom from cardiac death rate was 93.8%. After 1  year (1.3 ± 0.6  years) of follow-up, postoperative left ventricular ejection fraction increased significantly from 48.5 ± 19.6% to 55.4 ± 7.2% (p < 0.0001), LV end-systolic dimension index decreased significantly from 29.3 ± 11.8 to 18.5 ± 3.1 mm/m2 (p < 0.0001). Specifically, LV end-diastolic dimension decreased from 65.4 ± 22.6 mm to 60.84 ± 0.21 mm (p = 0.023) in the TAVR group vs. 67.3 ± 22.4 mm to 62.99 ± 0.29 mm (p = 0.204) in the MICS-AVR group. There was a steady and significant improvement in post-procedural LV septal thickness in both groups at different evaluation times. There was also a slight but significant improvement in LV dimensions (LV end-diastolic dimension and LV end-systolic dimension) in the TAVR group at 1 year compared with the MICS-AVR group.Conclusion. Favorable long-term outcomes, including 6-year freedom from cardiac mortality and no need for reoperation, were similar in both groups. Both TAVR and MICS-AVR are effective treatments for patients with aortic stenosis, allowing for the potentiation of postoperative LV remodeling and achieving satisfactory long-term outcomes and improved quality of life.